2012
DOI: 10.1007/s00339-012-6790-0
|View full text |Cite
|
Sign up to set email alerts
|

Binder-free composite electrodes using carbon nanotube networks as a host matrix for activated carbon microparticles

Abstract: In this research, networks of single-walled carbon nanotubes (SWNTs) were used to host activated carbon (aC) microparticles to fabricate freestanding composite electrodes without the use of polymer binders. The aC-SWNT composite electrodes with up to 50 wt. % aC showed specific surface areas approaching 1000 m 2 /g and electrical conductivities >36 S/cm. The composite electrodes possessed the properties of both pure SWNT electrodes (e.g. low ohmic drop and rapid ion diffusion) and activated carbon particles (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…This can be achieved by vacuum filtration of the stable suspension containing both CNTs and AC particles. [15,38,66] Experimental results also demonstrated that the flexible composite electrodes have much better performance compared with other electrodes made with traditional approaches. Flexible and binder-free CNTs/AC electrodes containing 95 wt% of AC were able to reach specific capacitance of 268 F/g at 200 mV/s in 6 M KOH.…”
Section: Flexible Electrodes Based On Composite Carbonmentioning
confidence: 60%
“…This can be achieved by vacuum filtration of the stable suspension containing both CNTs and AC particles. [15,38,66] Experimental results also demonstrated that the flexible composite electrodes have much better performance compared with other electrodes made with traditional approaches. Flexible and binder-free CNTs/AC electrodes containing 95 wt% of AC were able to reach specific capacitance of 268 F/g at 200 mV/s in 6 M KOH.…”
Section: Flexible Electrodes Based On Composite Carbonmentioning
confidence: 60%
“…In the case of the BP and CF interply hybrid composites, resin flow occurred in both nanoscale and microscale pores during the autoclave process. [28,33] According to the Young-Laplace equation, [34] the capillary pressure is in the inverse proportional relationship to the effective mean pore diameter. The throughthickness permeability of BP has been measured to be on the order of 10 À19 -10 À17 m 2 , [28] depending on CNT type, microstructure, surface characteristic, and so on.…”
Section: Resin Impregnation Mechanism In Autoclave Process For Bp/cf mentioning
confidence: 99%
“…This is likely caused by a strong capillary pressure for resin imbibitions due to an average nanoscale pore width of 11.66 nm in the BP layer, based on Brunauer-Emmett-Teller (BET) test. [28,33] According to the Young-Laplace equation, [34] the capillary pressure is in the inverse proportional relationship to the effective mean pore diameter. The diameter of IM7 fiber is 5.2 mm.…”
Section: Resin Impregnation Mechanism In Autoclave Process For Bp/cf mentioning
confidence: 99%
“…There are two approaches to this. One is to use a continuous Flocell to increase the efficiency and throughput of sonication . The Flocell is a continuous reactor that connected to a large tank of sample fluid.…”
Section: Introductionmentioning
confidence: 99%